The effect of CaO addition on the microstructural, mechanical and dielectric properties of pure MgO ceramic - Sutjipto, Agus Geter Edy (Trans Tech Publications, Switzerland, 2007)
High purity MgO is a common ceramic material used as a protecting layer in an alternating current plasma display panel (AC-PDP). In this work, pure MgO was added by CaO for a better protecting layer. The effect of CaO addition was discussed according to the changes in the microstructure, mechanical strength and the ability of the sample to withstand surface breakdown (flashover) with various CaO addition in the powder mixture. In addition, it was found that 2.5 wt% CaO-addition shows a better electrical discharge. Since secondary electron emission coefficient contributes in the electrical discharge, it could be predicted that the 2.5 wt% CaO added MgO has a higher secondary electron emission constant and becomes a promising candidate for a protecting layer in AC-PDP.